Peter Salner: Mozaika židovskej Bratislavy (Mosaic of Jewish Bratislava). : Bratislava: Albert Marenčin Vydavateľstvo PT, 2007, 199 pp., photographs, ISBN 978-80-89218-37-0. - Soukupová, Blanka (Lidé města, 2008)
A review of the book by Peter Salner.